2023
DOI: 10.3390/catal13061017
|View full text |Cite
|
Sign up to set email alerts
|

CO2 to Value-Added Chemicals: Synthesis and Performance of Mono- and Bimetallic Nickel–Cobalt Nanofiber Catalysts

John Schossig,
Akash Gandotra,
Kevin Arizapana
et al.

Abstract: In an epoch dominated by escalating concerns over climate change and looming energy crises, the imperative to design highly efficient catalysts that can facilitate the sequestration and transformation of carbon dioxide (CO2) into beneficial chemicals is paramount. This research presents the successful synthesis of nanofiber catalysts, incorporating monometallic nickel (Ni) and cobalt (Co) and their bimetallic blend, NiCo, via a facile electrospinning technique, with precise control over the Ni/Co molar ratios.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Following the fabrication step, these precursor composite nanofibers were subjected to a series of heat treatments under an inert atmosphere. The temperatures selected for these treatments, specifically 450, 850, 1050, and 1250 °C, have been consistently applied, as documented in our prior research . The goal of these treatments was to convert the Fe/Co salts to their metallic states and concurrently convert PAN to CNFs.…”
Section: Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Following the fabrication step, these precursor composite nanofibers were subjected to a series of heat treatments under an inert atmosphere. The temperatures selected for these treatments, specifically 450, 850, 1050, and 1250 °C, have been consistently applied, as documented in our prior research . The goal of these treatments was to convert the Fe/Co salts to their metallic states and concurrently convert PAN to CNFs.…”
Section: Results and Discussionmentioning
confidence: 99%
“…On the other end of the spectrum, metal loadings below 5% resulted in subpar hydrogenation performance, rendering the catalysts impractical for real-world applications . Additionally, our previous studies have indicated that a molar ratio of 1/2 (Fe/Co) is optimal for bimetallic nanofiber catalysts, promoting an enhanced electronic structure conducive to catalytic activity . Therefore, through recipe optimization, the Fe content was established at 5.00% and the Co content at 10.55% in the monometallic nanofibers (Table ).…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations